Antifungal Effect of Antimicrobial Photodynamic Therapy Mediated by Haematoporphyrin Monomethyl Ether and Aloe Emodin on Malassezia furfur - Cui, Zixin; Zhang, Miaomiao; Geng, Songmei; Niu, Xinwu; Wang, Xiaopeng; Zhu, Yanyan; Ye, Feng; Liu, Chengcheng (Frontiers in Microbiology, 2021)
Infectious dermatological diseases caused by Malassezia furfur are often chronic, recurrent, and recalcitrant. Current therapeutic options are usually tedious, repetitive, and associated with adverse effects. Alternatives that broaden the treatment options and reduce side effects for patients are needed. Antimicrobial photodynamic therapy (aPDT) is an emerging approach that is quite suitable for superficial infections. The aim of this study is to investigate the antimicrobial efficacy and effect of aPDT mediated by haematoporphyrin monomethyl ether (HMME) and aloe emodin (AE) on clinical isolates of M. furfur in vitro. The photodynamic antimicrobial efficacy of HMME and AE against M. furfur was assessed by colony forming unit (CFU) assay. The uptake of HMME and AE by M. furfur cells was investigated by fluorescence microscopy. Reactive oxygen species (ROS) probe and flow cytometry were employed to evaluate the intracellular ROS level. The effect of HMME and AE-mediated aPDT on secreted protease and lipase activity of M. furfur was also investigated. The results showed that HMME and AE in the presence of light effectively inactivated M. furfur cells in a photosensitizer (PS) concentration and light energy dose-dependent manner. AE exhibited higher antimicrobial efficacy against M. furfur than HMME under the same irradiation condition. HMME and AE-mediated aPDT disturbed the fungal cell envelop, significantly increased the intracellular ROS level, and effectively inhibited the activity of secreted protease and lipase of M. furfur cells. The results suggest that HMME and AE have potential to serve as PSs in the photodynamic treatment of dermatological diseases caused by M. furfur, but further ex vivo or in vivo experiments are needed to verify that they can meet the requirements for clinical practice.